Cognitive Flexibility, Attention and Speed of Mental Processing in Opioid and Methamphetamine Addicts in Comparison with Non-Addicts - Suzan Hekmat; Zahra Alam Mehrjerdi; Afsane Moradi; Hamed Ekhtiari; Sara Bakhshi (Basic and Clinical Neuroscience, 2011)
Introduction: Many studies have revealed that drug addicted individuals exhibit impaired performance on executive function tests but a few studies have been conducted on executive functions of drug addicts in Iran. To contribute to this understanding, the present study was designed to assess some domains related to executive functions including cognitive flexibility, attention and speed of mental processing in a sample of drug addicts in comparison with a sample of non-drug addicts. Methods: 155 male addicts between 25 to 35 years of age were selected from outpatient addiction clinics in Karaj, Iran. This group consisted of 3 subgroups of opium (n=40), hydrochloride heroin (n=63), and methamphetamine (n=52) addicts. A control group was selected matching the drug addicts in gender, age, education and scio-economic status and included 130 healthy non-drug taking males. A battery of standardized executive function tests including the Color trail making test, Stroop color word test, and Symbol digit modalities test were administered. Data analysis was conducted by performing Co-variance (MANCOVA) in SPSS.v.16.0. Results: The study findings indicated that the group of drug addicted subjects performed significantly worse compared with the controls on all executive measures. There were also significant differences among the 3 subgroups. The hydrochloride group had the worst performance compared the methamphetamine and opium groups respectively. Drug addicted subjects with longer duration of drug addiction were much worse on all measures in comparison with drug addicted subjects with shorter duration of drug addiction. Discussion: The study results confirmed that the functions of specific brain regions underlying cognitive flexibility, attention and speed of mental processing were significantly impaired in the group of drug addicted subjects. These impairments were also significantly related to type of drug used and duration of drug addiction that may contribute to most of behavioral disturbances found in drug addicts and need specific attention for intervention and treatment programs.